EEG findings in patients with angelman syndrome. Notched slow waves and age-specific characteristics of the main EEG patterns - G. V. Kuzmich; M. Yu. Bobylova; K. Yu. Mukhin; O. A. Pylaeva; L. Yu. Glukhova; A. S. Bagdasaryan; A. Yu. Zakharova (Русский журнал детской неврологии)
Angelman syndrome (AS) is a genetic disorder caused by a mutation in the maternal copy of the UBE3A gene and characterized by typical clinical manifestations (such as mental retardation, difficulty walking, and laughter) and specific changes on the electroencephalogram (EEG).The aim of this study was to analyze age-specific characteristics of the main EEG patterns, including high-amplitude frontal delta activity with spikes, slow-wave delta-theta activity with spikes in the posterior regions, and diffuse continuous rhythmic theta activity. In addition to that, we assessed the frequency of a rare and highly specific for AS EEG pattern: notched slow waves.We have identified and described additional criteria for EEG during sleep: high index of pathological slow-wave activity and the ratio of pathological slow-wave activity index to epileptiform activity index during sleep. We also analyzed all EEG patterns at the age most significant for the detection of this syndrome (up to 3 years) and their age-specific dynamics.We covered the frequency and characteristics of EEG patterns rare in AS patients, such as three-phase bifrontal delta waves, reactive pathological activity in the posterior areas, EEG patterns of focal seizures originating from the posterior areas, benign epileptiform discharges of childhood, and migrating continuous slow-wave activity.We analyzed the differences between main EEG patterns in AS and frontal and occipital intermittent rhythmic delta activity (fIRDA and OIRDA patterns).